2022
DOI: 10.1001/jamanetworkopen.2022.16715
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Missing Race and Ethnicity Information After Imputation in HealthCare.gov Marketplace Enrollment Data, 2015-2021

Abstract: This cross-sectional study examines patterns of missing information on race and ethnicity after an imputation of HealthCare.gov enrollment data between 2015 and 2021.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…To address the nearly 20% of Medicaid and 30% of marketplace enrollees who do not report their race or ethnicity, as well as misclassification of some Medicare beneficiaries based on previous Social Security categories of White, Black, and other, the HHS is currently using imputation and other methods. The results are already helping the HHS evaluate the effects of enrollment outreach campaigns and map health care disparities to social factors . Other efforts to enhance data include supporting community-level data sharing; expanding a comprehensive database on social determinants created by the Agency for Healthcare Research and Quality; adding information on food insecurity, housing, financial strain, and transportation to the data the HHS collects from community health centers and as part of national health surveillance efforts; and expanding the Office of the National Coordinator for Health Information Technology,…”
Section: Better Datamentioning
confidence: 99%
“…To address the nearly 20% of Medicaid and 30% of marketplace enrollees who do not report their race or ethnicity, as well as misclassification of some Medicare beneficiaries based on previous Social Security categories of White, Black, and other, the HHS is currently using imputation and other methods. The results are already helping the HHS evaluate the effects of enrollment outreach campaigns and map health care disparities to social factors . Other efforts to enhance data include supporting community-level data sharing; expanding a comprehensive database on social determinants created by the Agency for Healthcare Research and Quality; adding information on food insecurity, housing, financial strain, and transportation to the data the HHS collects from community health centers and as part of national health surveillance efforts; and expanding the Office of the National Coordinator for Health Information Technology,…”
Section: Better Datamentioning
confidence: 99%
“…Given the significant implicit and explicit bias many patients of colour face in the healthcare system, it is important to maintain this option in demographic surveys, while also providing information on how answers to this question will be used (e.g., to understand inequities in care, promote patient–provider concordance). This limitation is similar to other healthcare data sources: for example, 30% of enrollees in the https://Healthcare.gov Marketplace plans have missing race data, with rates as high as 63% in some states 5 . Better understanding disparities in maternal and digital health relies on the ability to accurately ascertain demographic data.…”
Section: Discussionmentioning
confidence: 83%
“…This limitation is similar to other healthcare data sources: for example, 30% of enrollees in the Healthcare.gov Marketplace plans have missing race data, with rates as high as 63% in some states. 5 Better understanding disparities in maternal and digital health relies on the ability to accurately ascertain demographic data. Second, Maven is only available to pregnant people who have the tools to access digital care.…”
Section: Discussionmentioning
confidence: 99%
“…In large surveys, it has been demonstrated that underrepresented minorities such as African Americans, Latinx, and Asian/Pacific Islanders are less likely to report their race than White survey respondents. 11,12 An important example of this in public health research was the finding that missing race data in COVID cases reported in Massachusetts did not occur randomly among all races and was most notable among minority races. 13 These findings of inequities in the time to treatment of syphilis along racial lines demands further investigation into contributory factors.…”
Section: Discussionmentioning
confidence: 99%